Investigation on dimensional accuracy of additive manufactured samples - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Sharum, Mohamad Afiq; Mohd Ali, Latifah (Penerbit UTM, 2024)
Fused deposition modelling (FDM) is a typical 3D printing process. Some benefits of FDM-printed components are durability, mechanical property stability, and the quality of the parts. However, it has several drawbacks, such as the emergence of seamlines between layers and the creation of extra material residue on the surface of the printed object, which compromises the dimensional accuracy of the printed part. When making pieces that fit correctly, the dimensions of 3D-printed components must be accurate. This article discusses the dimensional accuracy of 3D-printed components created using an open-source FDM 3D printer. The filament material for printing the test samples is stainless steel, ABS and tough PLA. The test samples were printed three times each and examined using a coordinate measuring machine (CMM). The geometries measured and compared between the three printed sample materials are the thickness, corner radius, angle, perpendicular, hole diameter, and flatness. The result shows that the printed samples could not achieve 100% dimensional accuracy, with stainless steel having the highest accuracy ranging from 99-98%. The data of stainless steel were then compared side by side with Tough PLA and ABS, where the accuracy of stainless steel is similar to ABS while PLA has the lowest accuracy. The accuracy of the stainless-steel specimen was then analysed and compared to tough PLA and ABS to identify the printing accuracy of the stainless-steel specimen, which is relatively new.